Down-Regulation of KV4 Channel in Drosophila Mushroom Body Neurons Contributes to Aβ42-Induced Courtship Memory Deficits. (1st February 2018) - Feng, Ge; Pang, Jie; Yi, Xin; Song, Qian; Zhang, Jiaxing; Li, Can; He, Guang; Ping, Yong
Graphical abstract: Cognitive normal (CN) males can learn from pairing with unreceptive mated females, whereas males with Alzheimer's disease (AD) persistently show courtship toward mated females after training, indicating loss of courtship memory in AD males. Aβ42-induced Kv 4 degradation and subsequent neuronal hyperexcitability in MBNs could be a major contributory cause of courtship memory loss. Highlights: Aβ42-expressing flies exhibit age-dependent courtship memory impairments. DNKv 4 mutants phenocopied Aβ42 flies in defective courtship memory. Restoration of Kv 4 expression rescues courtship memory deficits in Aβ42 flies. Kv 4 degradation in MBNs, in particular, is a major contributory cause of courtship memory loss in Aβ42 flies. Abstract: Accumulation of amyloid-β (Aβ) is widely believed to be an early event in the pathogenesis of Alzheimer's disease (AD). Kv 4 is an A-type K + channel, and our previous report shows the degradation of Kv 4, induced by the Aβ42 accumulation, may be a critical contributor to the hyperexcitability of neurons in a Drosophila AD model. Here, we used well-established courtship memory assay to investigate the contribution of the Kv 4 channel to short-term memory (STM) deficits in the Aβ42-expressing AD model. We found that Aβ42 over-expression in Drosophila leads to age-dependent courtship STM loss, which can be also induced by driving acute Aβ42 expression post-developmentally. Interestingly, mutants with eliminated Kv 4-mediated A-type K + currents (IA ) by transgenically expressing dominant-negative subunit (DNKv 4) phenocopied Aβ42 flies in defective courtship STM. Kv 4 channels in mushroom body (MB) and projection neurons (PNs) were found to be required for courtship STM. Furthermore, the STM phenotypes can be rescued, at least partially, by restoration of Kv 4 expression in Aβ42 flies, indicating the STM deficits could be partially caused by Kv 4 degradation. In addition, IA is significantly decreased in MB neurons (MBNs) but not in PNs, suggesting Kv 4 degradation in MBNs, in particular, plays a critical role in courtship STM loss in Aβ42 flies. These data highlight causal relationship between region-specific Kv 4 degradation and age-dependent learning decline in the AD model, and provide a mechanism for the disturbed cognitive function in AD.